Flux weakening control of Permanent Magnet Machine based aircraft electric starter-generator - Bozhko, Serhiy; Rashed, Mohamed; Yeoh, Seang Shen; Yang, Tao; Hill, Christopher Ian (2016)
This paper presents control analysis and design for an aircraft electric starter-generator system based on a Permanent Magnet Machine (PMM) operated in Flux-Weakening mode (FW). The focus is on detailed stability analysis which helped to discover an intrinsic instability when operating the PMM in FW mode. An adaptive voltage magnitude controller, including a variable current limit, is proposed and shown to guarantee stable operation. The analytical findings are verified by experimental investigation.